PENGARUH METODE PEMBELAJARAN REWARD DAN PUNISHMENT TERHADAP KEAKTIFAN BELAJAR SISWA SD KELAS V - Aniatul Khoirul Ummah; F. Shoufika Hilyana; Denni Agung Santoso (STKIP Subang, 2022)
The purpose of this study was to determine the effect of the application of reward and punishment learning methods on student learning activity in fifth grade mathematics at SD Negeri Tempaling. This research is a tye of quantitative research with quasi experimental methods. The instrument used was a questionnaire in the form of an observation sheet. The population inthis study werw fifth grade student at Tempaling Elementary School eith a total of 25 students. The data analysis technique used is normality test and regression linierity test as a prerequisite analysis test, descriptive data analysis, regression linierity test,significance test, sample linear regression test and the coefficient of determnination (D). The results showed that there was a positive and significant influence between the application of the reward and punishment learning method (X1) on student learning activity (Y) in class V at Tempaling Elementary School